Pra Kondisi untuk Pengelolaan Limbah Reflektor dari Reaktor Triga Mark II - Mulyono Daryoko (Seminar Nasional Teknik Kimia Kejuangan, 2015)
Pra Kondision Reflector For Managing Waste Of Reactor Triga Mark II. In 1996 there has been a refurbishment of the reactor Triga Mark II. The consequences of these events occur is the case of radioactive waste with a very significant amount. Waste is managed by the Radioactive Waste Technology Center. In this paper is presented the preparation of the waste management from the safety analysis before being taken to the placement on Radioactive Waste Technology Center. Radionuclide content contained in the reflector is H - 3, C - 14, Fe - 55, Co - 60, Eu - 152 and Eu - 154, with activities 1,0x104 Bq/ g, while the radiation is 66 rad/h. The conclusion of this study is the container used is a container cube shape with a length of 1097,3 mm, 624,2 mm width and height of 760,8 mm. The cube is coated with a steel plate of 12 mm and 8 mm . By conditioning, then to 200 mR / h. This means that the waste is safe both for workers and the environment.